Recruiting, Retaining and Engaging Men in Social Interventions: Lessons for Implementation Focusing on a Prison-based Parenting Intervention for Young Incarcerated Fathers. Issue 2 (3rd April 2018) - Buston, Katie
ABSTRACT: Recruiting, retaining and engaging men in social interventions can be challenging. The focus of this paper is the successful implementation of a parenting programme for incarcerated fathers, delivered in a Young Offender Institution (YOI) in Scotland. Reasons for high levels of recruitment, retention and engagement are explored, with barriers identified. A qualitative design was employed using ethnographic approaches including participant observation of the programme, informal interactions, and formal interviews with programme participants, the facilitators and others involved in managing the programme. Framework analysis was conducted on the integrated data set. The prison as the setting for programme delivery was both an opportunity and a challenge. It enabled easy access to participants and required low levels of effort on their part to attend. The creation of a nurturing and safe environment within the prison classroom facilitated engagement: relationships between the facilitators and participants, and between the participants themselves were key to understanding high levels of retention and engagement. The most fundamental challenge to high engagement levels arose from clashes in embedded institutional ways of working, between the host institution and the organisation experienced in delivering such intervention work. This threatened to compromise trust between the participants and the facilitators. Whilst adding specifically to the very sparse literature on reaching incarcerated young fathers and engaging them in parenting work, the findings have transferability to other under-researched areas: the implementation of social interventions generally in the prison setting, and engaging marginalised fathers in parenting/family work in community settings. The paper highlights ways of overcoming some of the challenges faced.